Problems of Criminalization of Crimes of Publishing through the Media: The Journalism Work Law in Kurdistan No. (35) of 2007 as a model - Omer, Shorsh Hassan; Hussein, Hawar Ibrahim (Journal of Legal and Political Studies, 2023)
Due to the importance of the role of the media in promoting societies as an important source of information, it cannot be dispensed with, but at the same time it can become a dangerous tool for society if the freedom of the media is misused or exploited through wrongful practice. Therefore, to avoid harm and to protect public and private interests, the legislator in most countries has criminalized those behaviors that could harm interests, by legislating special laws to regulate media work. However, the use of the weapon of criminalization by the legislator in the face of something that is of great importance in all societies, widely used, and guaranteed by charters and constitutions, is not an easy matter. The legislator must master the formulation of the criminal rules and texts restricting media work in an understandable, sound and accurate manner, free of defects and impurities in order to It protects public and private interests on the one hand, and protects public and private rights and freedoms, especially the right to freedom of information, on the other hand. We tried to shed light on the defects and problems of criminalizing crimes of publishing through the media in the Journalistic Work Law in Kurdistan No. (35) of 2007. This was done by dividing it into two sections. In the first section, we addressed the problem of the lack of legal certainty in media penal texts, by researching The error, deficiency and ambiguity in the penal text of the aforementioned law, and we presented solutions and proposals to solve the problem and maintain the principle of legal certainty. In the second section, we discussed the problem of the lack of balance in penal media texts, through the extent of the imbalance between interests when the legislator does not adhere to the accuracy and quality of the penal text, and the extent of his commitment to the principle of necessity and proportionality in establishing the principle of balance. In the end, we discussed the issue of the silence of the Kurdistan legislator regarding phenomena and behaviors that are harmful and threatening to public interests, which created a legislative vacuum in the legal regulation of media work.
Keywords: media; source of information; dangerous tool; private interests; criminalization